Canadian Arctic sea ice reconstructed from bromine in the Greenland NEEM ice core - Spolaor, Andrea; VALLELONGA, PAUL TRAVIS; TURETTA, Clara; Maffezzoli, Niccolò; COZZI, Giulio; GABRIELI, Jacopo; BARBANTE, Carlo; Goto Azuma, Kumiko; Saiz Lopez, Alfonso; Cuevas, Carlos A.; Dahl Jensen, Dorthe (Scientific Reports, 2016)
Reconstructing the past variability of Arctic sea ice provides an essential context for recent multi-year sea ice decline, although few quantitative reconstructions cover the Holocene period prior to the earliest historical records 1,200 years ago. Photochemical recycling of bromine is observed over first-year, or seasonal, sea ice in so-called "bromine explosions" and we employ a 1-D chemistry transport model to quantify processes of bromine enrichment over first-year sea ice and depositional transport over multi-year sea ice and land ice. We report bromine enrichment in the Northwest Greenland Eemian NEEM ice core since the end of the Eemian interglacial 120,000 years ago, finding the maximum extension of first-year sea ice occurred approximately 9,000 years ago during the Holocene climate optimum, when Greenland temperatures were 2 to 3 degrees C above present values. First-year sea ice extent was lowest during the glacial stadials suggesting complete coverage of the Arctic Ocean by multi-year sea ice. These findings demonstrate a clear relationship between temperature and first-year sea ice extent in the Arctic and suggest multi-year sea ice will continue to decline as polar amplification drives Arctic temperatures beyond the 2 degrees C global average warming target of the recent COP21 Paris climate agreement.